PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN UTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN STUDI KASUS PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX PERIODE 2013-2016 - Mohammad Faisol Efendi; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT                 This study aims to determine the effect of dividend variables, debt policy, profitability on firm value, to measure it using multiple linear methods, in this study are companies registered in the Jakarta Islamic Index 2013-2015 period which discusses 30 companies and samples in secret research 10 the company selected using purposive sampling method. The Jakarta Islamic Index of Companies will be corrected once every 6 months by the OJK. The results of this study indicate that partially the profitability variable has a significant effect on the value of the company (sig. 0,000), while the dividend policy variable, the policy is insignificant insignificant to the value of the company Keywords: Dividend Policy, Debt Policy, Profitability, Company Value